2012
DOI: 10.1007/s11356-012-0873-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cu, Zn, and Cd from aqueous solutions by the dairy manure-derived biochar

Abstract: Results indicated that dairy manure waste can be converted into value-added biochar as a sorbent for sorption of heavy metals, and the mineral components originated in the biochar play an important role in the biochar's high sorption capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
188
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(210 citation statements)
references
References 52 publications
12
188
2
4
Order By: Relevance
“…Biochar derived from waste biomass is now gaining much attention for its function as a biosorbent for environmental remediation (Xu et al 2013). In this perspective, sludge can be also transformed, e.g., into biofertilisers.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar derived from waste biomass is now gaining much attention for its function as a biosorbent for environmental remediation (Xu et al 2013). In this perspective, sludge can be also transformed, e.g., into biofertilisers.…”
Section: Introductionmentioning
confidence: 99%
“…The bark has higher contents of ash (2.5-5%), Al and Si than wood (<2%). As trace elements composition of lignocellulosic feedstock can influence the properties of biochar produced, Xu et al (2013) found that PO4 3-and CO3 2-served as additional adsorption sites, contributing to the dairy manure biochar's high adsorption capacity for Cu, Zn and Cd. Baltrėnaitė et al (2016a) established that for effective application in biofiltration systems, selected biochar should contain inorganic nutrients in sufficient quantity (nitrogen 0.4%, phosphorus 0.15%, potassium 0.15%).…”
Section: Modification Methods For Lignocellulosic Biochar Towards Enhmentioning
confidence: 99%
“…the enhancement in adsorption capacity of Cr(VI) may be due to the increased rate of intraparticle diffusion of Cr(VI) ions into the pores of the biochar at higher temperatures (Karthikeyan et al, 2005). When the pore size of the adsorbent is larger than the diameter of the molecules of the adsorbate, then Knudsen diffusion begins to play a significant role (Xu et al, 2013). The adsorption behaviour of biochar is well correlated with the properties of the PTE.…”
mentioning
confidence: 99%
“…Due to the presence of surface functional groups such as acetamido, alcoholic, carbonyl, phenolic, amido, amino, sulfhydryl groups, cellulosic agricultural waste materials act as an important source for metal biosorption. Effective metal biosorption was demonstrated by microalgae, sea weeds, bacteria, fungi, animal residues and agricultural residues (Can et al 2006;Kirbiyik et al 2012;Xu et al 2013;Din and Mirza 2013;Zhao et al 2012;Farnad et al 2012).…”
Section: Introductionmentioning
confidence: 99%